Examination of repeatability of ultrasound scanning technique in young bulls - Harangi, Sándor; Béri, Béla; Czeglédi, Levente (Acta Agraria Debreceniensis, 2008)
The author’s goal with the methodology examination was to determine repeatability of taking and evaluating ultrasound images. In the trial an operator person took two images about the ribeye area and rump fat thickness (P8) of every young bull, which were measured by the same person in four repetitions. Also, we had altogether eight images about the same part of the body. Images were collected using Falco 100 (Pie Medical) real-time ultrasonic scanner equipped with an ASP 3,5 MHz, 18 cm linear array transducer.